Code – Switching of the Novice Teachers in Filipino - Lazarte, Ma. Beatriz H. (Technium Social Sciences Journal, 2021)
This study is a Basic Qualitative Research Design. It’s about investigating the sole reasons for using code-switching and classifying them. The respondents of this study were teachers who teach Filipino at one of the Catholic universities in Bacolod City. All data from the the actual discussion and interview of the respondents were recorded and transcribed one by one. Purposive sampling was used in selecting the respondents. After the study, the researcher found out that there are various reasons for using code-switching in actual teaching and discussion, they are as follows; comprehension, lack of vocabulary and skills, inadvertently speaking, boredom out of using pure Filipino and the use of multilingual. There are four forms of code-switching that comes out, it is the intra-sentential, inter-sentential, tag switching and intra word switching. Out of four mentioned, intra-sentential code-switching was the most frequently used. The result of this study expands the understanding of why a teacher is code-switching on his or her teaching. In fact, code-switching helped students to fully understand the lesson which are being discussed if a teacher was using code-switching. Thus, the output of this study was a glossary which all code-switched words that the teachers used in his or her teaching was recorded.